High-Gain Textile Antenna Array System for Off-Body Communication - Maria Lucia Scarpello; Luigi Vallozzi; Hendrik Rogier; Dries Vande Ginste (International Journal of Antennas and Propagation)
A novel high-gain textile antenna array system, fully integrated into a rescue-worker’s vest and operating in the Industrial, Scientific, and Medical wireless band (2.4–2.4835 GHz), is presented. The system comprises an array consisting of four tip-truncated equilateral triangular microstrip patch antennas (ETMPAs), a power divider, line stretchers, and coaxial cables. The array is vertically positioned on the human torso to produce a narrow beam in elevation, as such reducing fading and allowing to steer the maximum gain in a small angular sector centered around the broadside direction. To allow simple low-cost beam steering, we specifically minimize mutual coupling by using a relative large distance between the patches and by selecting the ETMPA element as the most suited topology from three potential patch geometries. Moreover, we investigate the stability of return loss and mutual coupling characteristics under different relative humidity conditions, when bending the array, when placing the system on-body, and when covering it by different textile layers. Reflection coefficient and gain patterns are simulated and measured for the antenna system in free space and placed on the human body.